Pengaruh perbedaan jenis pakan terhadap pertumbuhan lobster laut, Panulirus versicolor - Makasangkil, Lestari; Salindeho, Indra R.N.; Lumenta, Cyska (Universitas Sam Ratulangi, 2017)
The aim of the research was to find out the growth rate of the marine lobster, Panulirus versicolor, fed different types of diets. The experiment was conducted at the Laboratory of Aquaculture Technology, Faculty of Fisheries and Marine Sciences, Sam Ratulangi University. The experiment was set up in 3 treatments, which were three different types of diet: treatment-A: papaya leaves, treatment-B: coconut flesh, treatment-C: skipjack-fish flesh. Each treatment was triplicated. The tested lobsters were collected from the marine waters of the Likupang village, North Minahasa Regency. The tested lobsters were weighed at the beginning, at the end of the experiment, and at the interval of 14 days during the experiment period. The data of the body weight change were statistically analysed using the analysis of the homogeneity of the 3 different linear regression coefficients, between time (X) and the body weight of the lobsters (Y) fed different types of feed, at the confidence test level a = 5% and 1%. The results show that the body weight of the tested lobsters fed skipjack-fish flesh increased 4 grams after 30 days of the rearing period. The body weight of the tested lobsters fed papaya leaves decreased 11 g, and the body weight of those fed coconut flesh decreased 3 g after 30 days of the rearing period. The result of the regression analysis shows, the assumption that the 3 regression coefficients are homogenous is rejected. In other words, there is a significant difference among the growth rates of the tested lobsters fed different type of diets. Compared to skipjack-fish flesh, the papaya leaves and coconut flesh significantly slow down the level of the water quality degradation during experiment period.Keywords: diets, growth, marine-lobster